Advances and challenges in modeling inherited peripheral neuropathies using iPSCs - Van Lent, J; Prior, R; Pérez Siles, G; Cutrupi, AN; Kennerson, ML; Vangansewinkel, T; Wolfs, E; Mukherjee-Clavin, B; Nevin, Z; Judge, L; Conklin, B; Tyynismaa, H; et al. (Springer Nature [academic journals on nature.com], 2024)
Inherited peripheral neuropathies (IPNs) are a group of diseases associated with mutations in various genes with fundamental roles in the development and function of peripheral nerves. Over the past 10 years, significant advances in identifying molecular disease mechanisms underlying axonal and myelin degeneration, acquired from cellular biology studies and transgenic fly and rodent models, have facilitated the development of promising treatment strategies. However, no clinical treatment has emerged to date. This lack of treatment highlights the urgent need for more biologically and clinically relevant models recapitulating IPNs. For both neurodevelopmental and neurodegenerative diseases, patient-specific induced pluripotent stem cells (iPSCs) are a particularly powerful platform for disease modeling and preclinical studies. In this review, we provide an update on different in vitro human cellular IPN models, including traditional two-dimensional monoculture iPSC derivatives, and recent advances in more complex human iPSC-based systems using microfluidic chips, organoids, and assembloids.